Analysis of fracture mechanism for surrounding rock hole based on water-filled blasting - Jun Wang; Jingxuan Yang; Fengfeng Wu; Tengfei Hu; Shams Al Faisal (International Journal of Coal Science & Technology, 2020)
Abstract The principles of fracture development during underwater blasting are examined based on explosion and impact dynamics, fluid dynamics, fracture dynamics, and field testing. The research reveals that the fracturing of the surrounding rock during underwater blasting is due to the combined action of shock and stress waves for the initial rock breakage and subsequent water expansion. The fracture development model for the surrounding rock of a drilling hole during underwater blasting is established. The rock fracturing range under the combined action of shock and stress waves is developed, as well as the fracture propagation rules after the wedging of the water medium into the fractures. Finally, the results of deep-hole underwater blasting tests on large rocks confirm the efficient utilization of explosive in the hole to improve the safety conditions. Accordingly, safe and static rock breaking under the detonation of high-effect explosive can be achieved. In addition, super-dynamic loading from the explosions and static loading from the water medium in the hole can be adequately combined for rock breaking.